2019
DOI: 10.1002/adma.201806790
|View full text |Cite
|
Sign up to set email alerts
|

Thinnest Nonvolatile Memory Based on Monolayer h‐BN

Abstract: Abstract2D materials have attracted much interest over the past decade in nanoelectronics. However, it was believed that the atomically thin layered materials are not able to show memristive effect in vertically stacked structure, until the recent discovery of monolayer transition metal dichalcogenide (TMD) atomristors, overcoming the scaling limit to sub‐nanometer. Herein, the nonvolatile resistance switching (NVRS) phenomenon in monolayer hexagonal boron nitride (h‐BN), a typical 2D insulator, is reported. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
224
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(243 citation statements)
references
References 31 publications
15
224
2
2
Order By: Relevance
“…We find a very low cycle to cycle variability in the memory ratio, defined as the ratio of the on and off state current, demonstrating the reliability of these non-volatile memory devices (inset of figure 3(d)). Furthermore, the memory ratio in our devices, which can be as high as 10 8 , is comparable to state of the art sensors fabricated with two-dimensional materials, that have reported in literature (Supplementary section C.2) [52][53][54][55][56][57][58][59]. Additionally, the low bias requirements and program state current value makes the device power efficient with an observed power dissipation of ≈10pW in the program state in our MoS 2 based memory devices [51].…”
supporting
confidence: 72%
“…We find a very low cycle to cycle variability in the memory ratio, defined as the ratio of the on and off state current, demonstrating the reliability of these non-volatile memory devices (inset of figure 3(d)). Furthermore, the memory ratio in our devices, which can be as high as 10 8 , is comparable to state of the art sensors fabricated with two-dimensional materials, that have reported in literature (Supplementary section C.2) [52][53][54][55][56][57][58][59]. Additionally, the low bias requirements and program state current value makes the device power efficient with an observed power dissipation of ≈10pW in the program state in our MoS 2 based memory devices [51].…”
supporting
confidence: 72%
“…This issue could be surmounted by the use of insulating h-BN [117] as active layer. By using CVD-synthesized monolayer h-BN, Wu et al fabricated memristive devices with the thinnest active layer (≈0.33 nm) and observed similar switching performance [113] with forming free feature (Figure 5c,d). [118] By pushing the thickness of active layer to atomic limit, Ge et al reported the first atomristor based on monolayer TMDs (i.e., MoS 2 , MoSe 2 , WS 2 , WSe 2 ).…”
Section: Wwwadvelectronicmatdementioning
confidence: 85%
“…Similar to the TMOs-based memristive devices, other ions migration, for example, B 3+ , N 3− and O 2− , in 2D layered materials have been proposed to account for the growth and rupture of filaments in vertical memristive devices; [57,60,80,109,112,113,129] It is well known that ions migration in conventional memristive devices causes the formation of filaments, while electricfield-induced S 2− migration in MoS 2 based planar structure memristive devices leads to the movement of grain boundaries and gives rise to resistive switching. Similar to the TMOs-based memristive devices, other ions migration, for example, B 3+ , N 3− and O 2− , in 2D layered materials have been proposed to account for the growth and rupture of filaments in vertical memristive devices; [57,60,80,109,112,113,129] It is well known that ions migration in conventional memristive devices causes the formation of filaments, while electricfield-induced S 2− migration in MoS 2 based planar structure memristive devices leads to the movement of grain boundaries and gives rise to resistive switching.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…In Figure 3e, the Raman peak at 1363.8 cm −1 of BNNS has a bathochromic‐shift compared to that of bulk h‐BN, which is due to the influence of the stretching vibration between the nanosheet and the Si/SiO 2 substrate used in the test on the E 2g vibration of BNNS. [ 30,31 ] As shown in Figure 3f, the Raman spectrum of graphene includes the emerging D band and D' band at ≈1350 and 1620 cm −1 , which are attributed to the structural and edge defects caused by the disordered vibration of graphene. Meanwhile, the Raman spectrum of the obtained graphene demonstrates an I D / I G ratio of 0.28, which is much smaller than that of chemically or thermally reduced GO (≈1.1−1.5) and electrochemically exfoliated graphene (0.4) in acidic solution, [ 32 ] indicating a smaller degree of defects in the as‐obtained graphene.…”
Section: Figurementioning
confidence: 99%